Cofilin-1 inactivation leads to proteinuria - Studies in zebrafish, mice and humans - Ashworth, Sharon; Teng, Beina; Kaufeld, Jessica; Miller, Emily; Tossidou, Irini; Englert, Christoph; Bollig, Frank; Staggs, Lynne; Roberts, Ian S. D.; Park, Joon-Keun; Haller, Hermann; Schiffer, Mario (PLoS ONE, 2010)
Background: Podocytes are highly specialized epithelial cells on the visceral side of the glomerulus. Their interdigitating primary and secondary foot processes contain an actin based contractile apparatus that can adjust to changes in the glomerular perfusion pressure. Thus, the dynamic regulation of actin bundles in the foot processes is critical for maintenance of a well functioning glomerular filtration barrier. Since the actin binding protein, cofilin-1, plays a significant role in the regulation of actin dynamics, we examined its role in podocytes to determine the impact of cofilin-1 dysfunction on glomerular filtration. Methods and Findings: We evaluated zebrafish pronephros function by dextran clearance and structure by TEM in cofilin-1 morphant and mutant zebrafish and we found that cofilin-1 deficiency led to foot process effacement and proteinuria. In vitro studies in murine and human podocytes revealed that PMA stimulation induced activation of cofilin-1, whereas treatment with TGF-β resulted in cofilin-1 inactivation. Silencing of cofilin-1 led to an accumulation of F-actin fibers and significantly decreased podocyte migration ability. When we analyzed normal and diseased murine and human glomerular tissues to determine cofilin-1 localization and activity in podocytes, we found that in normal kidney tissues unphosphorylated, active cofilin-1 was distributed throughout the cell. However, in glomerular diseases that affect podocytes, cofilin-1 was inactivated by phosphorylation and observed in the nucleus. Conclusions: Based on these in vitro and in vivo studies we concluded cofilin-1 is an essential regulator for actin filament recycling that is required for the dynamic nature of podocyte foot processes. Therefore, we describe a novel pathomechanism of proteinuria development. © 2010 Ashworth et al.
CRIS-Team Scopus Importer:2020-11-12